2009
DOI: 10.1002/dc.21104
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of metastatic pancreatic mesenchymal tumors by endoscopic ultrasound‐guided fine‐needle aspiration

Abstract: Involvement of the pancreas by metastatic sarcoma is rare, and can prove challenging to differentiate from sarcomatoid carcinomas which occur more commonly. The endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) technique has been successfully used for the diagnosis of pancreatic carcinomas whether primary or metastatic, and is now considered the most effective noninvasive method for the identification of pancreatic metastases. However, to date very few reports detail the diagnosis of mesenchymal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In the current study cohort, all the patients with carcinoma, melanoma, and sarcoma had previously documented disease and underwent EUS‐FNA for either staging purposes or to document metastatic/recurrent disease. The use of EUS‐FNA for documenting metastatic sarcoma is especially rare, but 1 study recently reported the successful use of EUS‐FNA for the diagnosis of leiomyosarcoma, liposarcoma, alveolar rhabdomyosarcoma, and solitary fibrous tumor that were all metastatic to the pancreas 58. For patients with spindle cell lesions who are undergoing EUS‐FNA for initial tissue diagnosis such as the patient with SFT, the acquisition of sufficient materials for an adequate cell block is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study cohort, all the patients with carcinoma, melanoma, and sarcoma had previously documented disease and underwent EUS‐FNA for either staging purposes or to document metastatic/recurrent disease. The use of EUS‐FNA for documenting metastatic sarcoma is especially rare, but 1 study recently reported the successful use of EUS‐FNA for the diagnosis of leiomyosarcoma, liposarcoma, alveolar rhabdomyosarcoma, and solitary fibrous tumor that were all metastatic to the pancreas 58. For patients with spindle cell lesions who are undergoing EUS‐FNA for initial tissue diagnosis such as the patient with SFT, the acquisition of sufficient materials for an adequate cell block is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, metastases comprise at least 2% of pancreatic tumors. [5] These metastases arise from a diverse spectrum of malignancies, including sarcomas,[6] Merkel cell carcinoma,[7] squamous cell carcinoma,[8] cardiac rhabdomyosarcoma,[9] ovarian mixed müllerian tumor,[10] melanoma,[11] and phyllodes tumor. [12] In such cases, accurate diagnosis is extremely important because treatment frequently differs.…”
Section: Introductionmentioning
confidence: 99%
“…5Y7 Pancreatic metastases (PM) may arise most frequently from the lung, kidney, breast, and colon. 8,9 Rare origins of PM include sarcomas, 10 Merkel cell carcinoma, 11 squamous cell carcinoma, 12 cardiac rhabdomyosarcoma, 13 ovarian mixed Mullerian tumor, 14 melanoma, 15 phylloides tumor, 16 adenoid cystic carcinoma, 17 as well as small bowel, stomach, liver, and urinary bladder tumors.…”
mentioning
confidence: 99%